2021
DOI: 10.1088/1361-6595/ac0b56
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive understanding of the ignition process of a pulsed capacitively coupled radio frequency discharge: the effect of power-off duration

Abstract: The effect of the pulse-off duration on the time evolution of the plasma and electrical parameters during the ignition phase in a pulsed capacitively coupled radio frequency argon discharge operated at 450 mTorr and 12.5 MHz is investigated synergistically by multifold experimental diagnostics, particle-in-cell/Monte Carlo collision simulations and an analytical model. In the experiment, the electron density is measured time-resolved by a hairpin probe, the spatio-temporal distribution of the electron impact e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 69 publications
3
30
0
Order By: Relevance
“…It is still unclear how the plasma parameters are involved during the breakdown process. The evolution of the plasma parameters and the transformation of the heating mode were recently observed in experiments by Liu et al [25] and Wang et al [26].…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…It is still unclear how the plasma parameters are involved during the breakdown process. The evolution of the plasma parameters and the transformation of the heating mode were recently observed in experiments by Liu et al [25] and Wang et al [26].…”
Section: Introductionmentioning
confidence: 65%
“…However, the above research all focused on the breakdown process of argon, a well-studied electropositive gas [25][26][27][28][29]. Compared to argon, discharges in electronegative gases such as CF 4 are quite different [9,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that during the initial stage of the pulse-on period, the input power exhibits two maxima, and meanwhile the electron density was observed to exhibit an overshoot at a high power and a low pressure. Wang et al [109] investigated the effect of the power-off duration on the plasma ignition process of a pulse modulated CCP operated in 450 mTorr Ar by a combination of experiments, PIC/MCC simulations, and an analytical model. They found that the time evolution of the plasma and electrical parameters during the ignition process depend strongly on the duration of the afterglow period, T off , due to the dependence of the remaining (or initial) charge density on this parameter.…”
Section: -12mentioning
confidence: 99%
“…Previous studies on the ignition process of a pulse modulated CCP mostly focused on the time evolution of the axially resolved or even spatially averaged plasma parameters (e.g., the plasma emission, the electron density and temperature, etc. ), [104,105,[109][110][111][112][113][114] however, a 300 mm-diameter electrode is used in current semiconductor industries and, therefore, time evolution of various plasma parameters is highly radius-dependent during the ignition process in a pulse modulated plasma. Su et al [115] studied, for the first time, the time evolution of discharge parameters at different radial positions over a 300 mm-diameter electrode during the ignition process of a pulse modulated CCP in argon by multi-fold experimental diagnostics.…”
Section: -12mentioning
confidence: 99%
“…Yong-Xin Liu et al find a sequence of distinct electron power absorption modes in gas discharge system [19]. The effect of the pulse-off duration on the plasma and electrical parameters in a pulsed capacitively coupled radio frequency argon discharge is investigated synergistically through experiment and simulation by Xiang-Yu Wang et al [20]. Only a few works observed the entire process of breakdown to identify the changes in it by means of computational analysis.…”
Section: Introductionmentioning
confidence: 99%